STORAGE MANAGEMENT OF CLINICAL RESEARCH SUPPLIES OF A PHASE IIB/III, NATIONAL, MULTI-CENTRE, DOUBLE-BLIND AND RANDOMIZED STUDY - Kawamoto Junior, Luiz Teruo; da Silva, Adriano Maniçoba; Ferreira, William de Paula; Rodrigues, Enio Fernandes; Harada, Lila M. (Brazilian Journal of Operations & Production Management, 2016)
Abstract: New drugs suffer a long and slow proceeding to reach the market. On the one hand there are difficulties from the regulatory agency that delays the onset of clinical trial studies, on the other hand there is a slow patient recruitment during the course of the trial that prevents its completion. An efficient management of clinical trial supplies throughout the supply chain is essential. Thus, the objective of this study was to characterize the clinical supplies storage management in a national, multi-centre, double-blind and randomized study to evaluate the efficiency and safety of a combination of drugs to treat acute pain. The study was primarily focused on storage conditions of clinical supplies, detailing their distribution to the research sites. According to the data observed in this study, the clinical supplies storage management was not determinant for the slow patient recruitment process that reflected the delay to the end of the study. And although the centers were located in different states, there were no delays, loss or damage during storage and distribution that could compromise the proper stock and storage management of clinical trial supplies.